Manipulating of Audio-Visual Aids in the Educational Processes in Al-Hilla University College - Fanukh Abbas, Chassib (International Journal of Psychosocial Rehabilitation, 2020)
The present study is about manipulating of audio-visual aids in Al-Hilla University College. The study was based on attaining the following objectives: To evaluate how the library meets the needs of the lecturers in the supply of audiovisual aids, the kinds and quality of audiovisual aids available in the college, their frequencies of use and inhibitions, and finally, what procedures the librarian has adopted in promoting or creating an awareness of the available audiovisual aids in the library. Two sets of questionnaires were administered to staff in order to state the needed information. The researcher also went to the college to observe and also to administer the questionnaire. Through the questionnaire and observation made by the researcher, data were gathered, organized, and analyzed using non-parametric statistical devices like percentages and frequencies; the mean was also used in research question three for easy analysis and discussion because of the number of the items included. It was finally found out that the college collection of audiovisual aids is fairly adequate. The lecturers in the college rarely use audiovisual aids in teaching. The whiteboard is the only audiovisual aid frequently manipulated by the lecturers. Non-availability, lack of enhancing infrastructures, and human factors are obstacles to the use of audiovisual aids in the college. There are various advantages that learners derive from using audiovisual aids. The awareness of available audio-visual aids created by the librarian is not impressive.